In vivo noninvasive three‐dimensional (3D) assessment of microwave thermal ablation zone using non‐contrast‐enhanced x‐ray CT. Issue 10 (21st August 2020) - Ziv, Omri; Goldberg, S. Nahum; Nissenbaum, Yitzhak; Sosna, Jacob; Weiss, Noam; Azhari, Haim
Abstract : Purpose: To develop an image processing methodology for noninvasive three‐dimensional (3D) quantification of microwave thermal ablation zones in vivo using x‐ray computed tomography (CT) imaging without injection of a contrast enhancing material. Methods: Six microwave (MW) thermal ablation procedures were performed in three pigs. The ablations were performed with a constant heating duration of 8 min and power level of 30 W. During the procedure images from sixty 1 mm thick slices were acquired every 30 s. At the end of all ablation procedures for each pig, a contrast‐enhanced scan was acquired for reference. Special algorithms for addressing challenges stemming from the 3D in vivo setup and processing the acquired images were prepared. The algorithms first rearranged the data to account for the oblique needle orientation and for breathing motion. Then, the gray level variance changes were analyzed, and optical flow analysis was applied to the treated volume in order to obtain the ablation contours and reconstruct the ablation zone in 3D. The analysis also included a special correction algorithm for eliminating artifacts caused by proximal major blood vessels and blood flow. Finally, 3D reference reconstructions from the contrast‐enhanced scan were obtained for quantitative comparison. Results: For four ablations located >3 mm from a large blood vessel, the mean dice similarity coefficient (DSC) and the mean absolute radial discrepancy between the contours obtained from the reference contrast‐enhanced images and the contours produced by the algorithm were 0.82 ± 0.03 and 1.92 ± 1.47 mm, respectively. In two cases of ablation adjacent to large blood vessels, the average DSC and discrepancy were: 0.67 ± 0.6 and 2.96 ± 2.15 mm, respectively. The addition of the special correction algorithm utilizing blood vessels mapping improved the mean DSC and the mean absolute discrepancy to 0.85 ± 0.02 and 1.19 ± 1.00 mm, respectively. Conclusions: The developed algorithms provide highly accurate detailed contours in vivo (average error < 2.5 mm) and cope well with the challenges listed above. Clinical implementation of the developed methodology could potentially provide real time noninvasive 3D accurate monitoring of MW thermal ablation in‐vivo, provided that the radiation dose can be reduced.